Verification of a virtual lunar regolith simulant - Louca, Joe; Vrublevskis, John; Eder, Kerstin; Tzemanaki, Antonia (Frontiers in Space Technologies, 2024)
Introduction: Physical regolith simulants are valuable tools for developing In-Situ Resource Utilisation hardware. However, using virtual models of regolith instead can reduce costs, limit exposure to hazardous materials, and offer a practical method of testing the effects of reduced gravity.We verify a virtual model of regolith as macroparticles against physical tests. Using space partitioning techniques to identify neighbouring particles, we present a scalable model of regolith, in which the computation time increases roughly proportionally with the number of particles. We evaluated the performance of this virtual simulant vs a physical simulant (Exolith LMS-1) by comparing the flow rate through funnels of various diameters, and the resultant angle of repose of material on both large (500 g) and small (16 g) scale tests.Results: For large scale tests, the flow rates were within the predicted range for macroparticles with radii 3-7 mm, with the greatest accuracy achieved for radii 4-5 mm. However, the macroparticles blocked the simulated funnels more easily than in the physical trials, due to their high cohesion. The angle of repose was not accurately represented by this model for either of the tests.The high efficiency of this model makes it best suited for applications which require large scale approximations of regolith with real-time execution, such as virtual training for robot operators or providing visual and haptic feedback in model-mediated teleoperation systems. The results of this model in reduced gravity could be further verified against data from upcoming lunar missions in future work.